Identifying Fire Blight-Resistant Malus sieversii Rootstocks Grafted with Cultivar ‘Aport’ Using Monitoring Data - Aisha Taskuzhina; Alexandr Pozharskiy; Zhulduzay Jumanova; Sagi Soltanbekov; Zhanna Issina; Nazym Kerimbek; Anastasiya Kapytina; Marina Khusnitdinova; Abay Sagitov; Alibi Darubayev; Aigerim Seisenova; Yerlan Omarov; et al. (Horticulturae, 2024)
In the present study, the most valuable cultivar ‘Aport krovavo-krasnyy’ was grafted onto M. sieversii genotypes harvested from 11 populations in Dzungarian Alatau and Ile Alatau to identify ones resistant to Erwinia amylovora. The wild apple populations included in the present research have not been previously explored. Seedling population 10, developed using rootstocks from a M. sieversii population growing in Turgen, demonstrated the highest resistance to Erwinia amylovora, showing no fire blight symptoms and no positive PCR results for E. amylovora during the eight years of monitoring in the Talgar field (Kazakhstan) from 2015 to 2022. The population from Steep Tract (seedling population 1) was also valuable for breeding and reduced the pathogen distribution to below 30%. Genotypes from a genetic reserve (seedling population 5) were the most susceptible among the researched populations, with a disease distribution level of 24–95%. In seedling population 5, trees affected at least twice by the pathogen exhibited wilting, shepherd’s crook formation, leaf necrosis, and occasional exudate droplets, while trees in other combinations primarily showed shoot wilting and leaf death. Fire blight disease also developed more rapidly within the plant in seedling population 5; by 2020, one tree nearly died after only two infections.